Genomic analysis of the marine fish pathogen Photobacterium damselae subsp. piscicida: Insertion sequences proliferation is associated with chromosomal reorganisations and rampant gene decay. - Balado, Miguel; Benzekri, Hicham; Labella Vera, Alejandro Manuel; Claros-Díaz, Manuel Gonzalo; Manchado, Manuel; Borrego-García, Juan José; Osorio, Carlos; Lemos, Manuel (Elsevier, 2017)
Photobacterium damselae subsp. piscicida (Pdp) is an intracellular fish pathogen that causes photobacteriosis, a disease proven deadly in farmed fish worldwide. This work focuses on the analysis of genome sequences, chromosomes structure and gene contents of two strains fromSparus aurata (DI21) and Solea senegalensis (L091106- 03H), isolated on the Spanish Atlantic coast. The comparative genomic analysis revealed that DI21 and L091106- 03H share 98% of their genomes, including two virulence plasmids: pPHDP70 encoding siderophore piscibactin synthesis and pPHDP10 encoding the apoptotic toxin AIP56. Both genomes harbour a surprisingly large number of IS elements accounting for 12–17% of the total genome, representing an IS density of 0.15 elements per kb, one of the highest IS density values in a bacterial pathogen. This massive proliferation of ISs is responsible for the generation of a high number of pseudogenes that caused extensive loss of biological functions. Pseudogene formation is one of the main features of Pdp genome that explains most of the ecological and phenotypic differences with respect to its sibling subspecies P. damselae subsp. damselae and to other Vibrionaceae. Evidence was also found proving the existence of two chromosomal configurations depending on the origin of the strains: an European and an Asian/American types of genome organisation, reinforcing the idea of the existence of two geographically- linked clonal lineages in Pdp. In short, our study suggests that the host-dependent lifestyle of Pdp allowed massive IS proliferation and gene decay processes, which are major evolutionary forces in the shaping of the Pdp genome.
https://v2.sherpa.ac.uk/id/publication/16825
Keywords: Peces - Agentes patógenos; Photobacterium damselae subsp. piscicida; Genome analysis; Fish pathogens; Marine bacteria; Virulence factors; Insertion sequences